2021
DOI: 10.1108/ejm-10-2019-0808
|View full text |Cite
|
Sign up to set email alerts
|

Green information quality and green brand evaluation: the moderating effects of eco-label credibility and consumer knowledge

Abstract: Purpose This study aims to examine the effects of three green information quality dimensions – persuasiveness, completeness and credibility – on green brand evaluation and whether this is mediated by green brand credibility. It also examines the moderating effects of eco-label credibility and consumer knowledge on green information quality dimensions and green brand credibility relationships. Design/methodology/approach Using a structured questionnaire on environmentally-friendly electrical goods/electronics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 166 publications
(268 reference statements)
2
53
1
2
Order By: Relevance
“…From the viewpoint of green marketing instruments, such a phenomenon, however, was marginally studied in India as against other Asian and emerging nations underpinned by the measures such as environmental labels, environmental brands, environmental advertisements, eco-trust (Chin et al, 2018;Chen et al, 2020;Kumar et al, 2021). Therefore, the present study postulates a conceptual model and examined based on "self-beliefsbehaviour" relationship, incorporating consumers' perception towards the three green marketing tools namely, eco-label, eco-brand, advertisements along with the cognitive measure of perceived environmental knowledge to predict the phenomenon of green purchasing behaviour in the backdrop of the Indian market.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the viewpoint of green marketing instruments, such a phenomenon, however, was marginally studied in India as against other Asian and emerging nations underpinned by the measures such as environmental labels, environmental brands, environmental advertisements, eco-trust (Chin et al, 2018;Chen et al, 2020;Kumar et al, 2021). Therefore, the present study postulates a conceptual model and examined based on "self-beliefsbehaviour" relationship, incorporating consumers' perception towards the three green marketing tools namely, eco-label, eco-brand, advertisements along with the cognitive measure of perceived environmental knowledge to predict the phenomenon of green purchasing behaviour in the backdrop of the Indian market.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature studied how environmental advertisements carve out consumers' favourable perception and trust towards ads' claims (Banerjee et al, 1995;Chang, 2011;Tucker et al, 2012) and how such perceptions affect their buying decision of green brands and eco-label (Kumar et al, 2021). Concerning this, scholars (Chang, 2011;Kumar et al, 2021;Tucker et al, 2012) found that environmental advertisement enhances consumers' green cognizance and persuasiveness towards green brands and labels, which further influence their purchase decision-making for sustainable product consumption.…”
Section: Perception Of Environmental Advertisements According Tomentioning
confidence: 99%
See 3 more Smart Citations